Intimate partner violence and consistent condom use among drug-using heterosexual women in New York City - Panchanadeswaran, Subadra (2010)
The present study examined the associations of relationship factors, partner violence, relationship power, and condom-use related factors with condom use with a main male partner among drug-using women. Over two visits, 244 heterosexual drug-using women completed a cross-sectional survey. Multivariate logistic regression models indicated that women who expected positive outcomes and perceived lower condom-use barriers were more likely to report condom use with their intimate partners. The findings suggest that future interventions aiming at reducing HIV risk among drug-using women should focus on women’s subjective appraisals of risks based on key relationship factors in addition to the occurrence of partner violence.